Insecticidal activity of phenolic acid amides against brown planthopper (BPH), Nilaparvata lugens (Stål) and their QSAR analysis. Issue 6 (3rd June 2019) - Kaushik, Parshant; Sarkar, Dhruba J.; Chander, Subhash; Rana, Virendra S.; Shakil, Najam A.
Abstract: A series of 42 phenolic acid amides, synthesized using different phenolic acids (salicylic acid, 3-hydroxy cinnamic acid, p-coumaric acid, caffeic acid, ferulic acid, o-coumaric acid, cinnamic acid and amines (propyl amine, hexyl amine, heptyl amine, undecyl amine, hexadecyl amine, octadecyl amine) were screened for their insecticidal activities against Brown Planthopper (BPH), Nilaparvata lugens . These phenolic acid amides showed moderate to good insecticidal activity with the lowest LC50 value of 63.84 ppm from N-propyl-2-hydroxycinnamamide. 2D-Quantitative structural activity relationship (2D-QSAR) analysis of these phenolic acid amides was carried out by developing three different models namely multiple linear regression (MLR), principal component regression (PCR) and partial least squares (PLS). Statistical significance and predictive ability of these models were assessed by internal and external validation and verified by leave one-out cross-validation. PLS (model 3) was found best for QSAR study with correlation coefficient ( r 2 ) 0.8388, cross-validated correlation coefficient ( q 2 ) 0.7797 and r 2 pred 0.7347. It was found that + vePotentialSurfaceArea, XAMostHydrophobic, SaasCE-index, T_O_O_3 and T_O_O_6 are the major descriptors which influence the insecticidal activities of these phenolic acid amides. The QSAR study could help in structural optimization of phenolic acid amides in developing potential compounds to get better bioefficacy against N. lugens .